(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
Simeulue Regency is surrounded by small islands rich in diverse fish resources, namely dogtooth tuna. The interaction (reciprocity) between groups of organisms and their environment plays an important role in ecological systems. The determination of ecological status can be used to monitor, manage, and sustain waters in tuna fishing areas. Fishing activities will affect environmental changes that will impact marine biota’s sustainability, existence, and diversity. This study aimed to analyze the ecological sustainability status of tuna fishing areas in East Simeulue waters. The research was conducted in May-July 2021. The method used in this research was observing and measuring the characteristics of the aquatic environment and conducting interviews. The attributes seen include the condition of the aquatic environment, conservation of pelagic resources, fishing activities, utilization of pelagic resources, environmental carrying capacity, type of fishing gear, the volume of fishing gear, level of suitability for fishing. The sustainability status of the ecological dimension obtained a value of 79.74. The results obtained are classified as well sustainable.